Tuning in Higher Education: Ten years on - Julia María González Ferreras; Robert Wagenaar (Universidad de Deusto, 2023)
When the first issue of the Tuning Journal for Higher Education was published in November 2013, the Tuning initiative had become of global significance, running projects in all continents. These all focussed on curriculum reform backed up by an internationally defined approach based on the paradigm of outcome based, that is, student-centred and active learning, in addition to agreed reference points. Around the same time, the Tuning aims and objectives were extended. This reset followed societal and technical developments. More emphasis was put on social inclusions, the involvement of students, identifying relevant topics, and to the development of practical tools. Also, more attention has been given to staff development responding to the notion that the modernisation of the higher education sector as well as the reform of degree programmes proved to be rather slow and a bit disappointing. To boost the process, Tuning - very recently - developed general Qualifications Reference Frameworks for all learning cycles as well as a Guideline to use these for Quality Assurance. For five disciplinary fields it also developed transnational diagnostic tests as a means to identify shortcomings in degree programmes, pushing for change. As a result, Tuning has reinvented itself to stay highly relevant for the years to come.